1986
DOI: 10.1038/324380a0
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent mutations in haemophilia A give evidence for CpG mutation hotspots

Abstract: Haemophilia A is a common disorder of blood coagulation caused by a deficiency of factor VIII. It is inherited as an X-linked recessive trait, and one-third of all cases are thought to result from de novo mutations. The clinical severity of haemophilia A varies markedly among different families and a subset of the patients with severe disease develop antibodies against factor VIII, called inhibitors. Because of this heterogeneity, it is likely that many different molecular lesions result in haemophilia A. Inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
100
0
2

Year Published

1988
1988
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 237 publications
(105 citation statements)
references
References 19 publications
3
100
0
2
Order By: Relevance
“…Anti-factor VIII antibodies (inhibitor) have been reported among patients caused by nonsense mutation in exon 18 (Higuchi et al, 1987;Matthews et al, 1987), 23 (Matthews et al, 1987), 24 (Gitschier et al, 1985;Higuchi et al, 1987) and26 (Higuchi et al, 1987) but not by nonsense mutation in exon 22 (Youssoufian et al, 1986;Higuchi et al, 1987). It has been also reported that missense mutations in exons 24 (Bernardi et al, 1987) and 26 (Gitschier et al, 1986) can cause a formation of anti-factor VIII antibodies (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anti-factor VIII antibodies (inhibitor) have been reported among patients caused by nonsense mutation in exon 18 (Higuchi et al, 1987;Matthews et al, 1987), 23 (Matthews et al, 1987), 24 (Gitschier et al, 1985;Higuchi et al, 1987) and26 (Higuchi et al, 1987) but not by nonsense mutation in exon 22 (Youssoufian et al, 1986;Higuchi et al, 1987). It has been also reported that missense mutations in exons 24 (Bernardi et al, 1987) and 26 (Gitschier et al, 1986) can cause a formation of anti-factor VIII antibodies (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The TaqI restriction site (TCGA) containing CpG dinucleotide are frequently examined in haemophiliacs by Southern blotting. Thus far, either the CpG--,TpG mutation (Antonarakis et al, 1985;Gitschier et al, 1985;Youssoufian et al, 1986Youssoufian et al, , 1987bHiguchi et al, 1987;Matthews et aL, 1987) or CpG--+ CpA mutation (Gitschier et al, 1986;Bernaldi et aL, 1987) has been observed in exons 18, 23, 24, and 26 of factor VIII gene. CpG --, TpG change caused a nonsense mutation from CGA (Arg) to TGA (stop codon), and the CpG -, CpA change caused a missense mutation from CGA (Arg) to CAA (Gin).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and moderate haemophilia A. Deletions in the factor VIII gene are reported to be associated with increased tendency for inhibitor development because of incorrect protein folding resulting in exposure of immunogenic epitopes that are usually buried within the protein core (Youssouffian et al, 1987;Gouw et al, 2007Gouw et al, , 2011. Specific mutation hotspots are 5-methylated cytosine residues which are readily deaminated to thymine (Youssoffian, 1986). These mutations usually result in introduction of premature stop codon (transition CGATGA) and, ultimately, in a truncated protein.…”
Section: Nature Of the Causative Mutationmentioning
confidence: 99%
“…The genetic heterogeneity of haemophilia patients suggests that many different molecular alterations are involved in the resultant malfunctional factor VIII gene in haemophiliacs. Several point and deletion mutations in the factor VIII gene were observed in Caucasian population (Gitschier et al, 1985(Gitschier et al, , 1986Antonarakis et al, 1985;Youssoufian et al, 1986Youssoufian et al, , 1987aYoussoufian et al, , 1987bHiguchi et al, 1987;Bernardi et aL, 1987;Matthews et al, 1987).…”
Section: Introductionmentioning
confidence: 99%